Data Management Technologies and Applications: 9th International Conference, DATA 2020, Virtual Event, July 7-9, 2020, Revised Selected Papers - Hammoudi, Slimane; Quix, Christoph; Bernardino, Jorge (Communications in Computer and Information Science, 2021)
This book constitutes the thoroughly refereed proceedings of the 9th International Conference on Data Management Technologies and Applications, DATA 2020, which was supposed to take place in Paris, France, in July 2020.